Factors that Influence the Decision to Choose Consumer Credit at PT BPR Baturaja (Perseroda) With Age as a Moderating Variable - Rahma Delawati; Sulastri; Aslamia Rosa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
As individuals age, they typically acquire more financial obligations, such as funding their children's education or planning for retirement, which can impact their decision to utilize consumer credit. This study aims to investigate the factors influencing the decision to opt for consumer credit at PT BPR Baturaja (Perseroda), with age serving as a moderating variable. The research methodology employed is associative descriptive research. The sampling technique utilized is probability random sampling, determined by the Slovin formula, resulting in a total sample size of 322. Data analysis was conducted using the Partial Least Square (PLS) method. The research findings lead to several conclusions: Firstly, service quality exerts a positive and significant influence on the decision to choose consumer credit at PT BPR Baturaja (Perseroda). Secondly, promotion demonstrates a positive but statistically insignificant effect on the decision to choose consumer credit at PT BPR Baturaja (Perseroda). Lastly, the interest rate has a positive and significant impact on the decision to select consumer credit at PT BPR Baturaja (Perseroda). The age variable acts as a Quasi Moderator (Quasi Moderation) on the influence of service quality on the decision to choose consumer credit at PT BPR Baturaja (Perseroda). The age variable acts as a Moderation Predictor on the influence of promotions on the decision to choose consumer credit at PT BPR Baturaja (Perseroda). The age variable acts as a Pure Moderator on the influence of interest rates on the decision to choose PT BPR Baturaja (Perseroda) consumer credit.